If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 + 2(-4x + 2) = -15 Reorder the terms: 4x + -3 + 2(2 + -4x) = -15 4x + -3 + (2 * 2 + -4x * 2) = -15 4x + -3 + (4 + -8x) = -15 Reorder the terms: -3 + 4 + 4x + -8x = -15 Combine like terms: -3 + 4 = 1 1 + 4x + -8x = -15 Combine like terms: 4x + -8x = -4x 1 + -4x = -15 Solving 1 + -4x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = -15 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = -15 + -1 -4x = -15 + -1 Combine like terms: -15 + -1 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| -6+(-36)x=30 | | 14=-7(p-8) | | B+9=16 | | n=1990-2000 | | 5p+60=11p | | -10+(-70)x-7=-87 | | 3x+4+3x+2=180 | | 20-g-g=14 | | 57=5x | | -15=2x-4+(2x+5) | | .45=169.8X | | 10(x-1)=44 | | 50=-4+3m | | y+9=5.4 | | 74=-7+63b+18 | | -3(3m)=3m-6 | | -2+n=-11 | | 18x=-288 | | 3(9s+2)-18s=3(3s+6)-22 | | -24=4/3(6n+12) | | 2(n+3)+4(8+6)=13n | | -.75y=.125 | | 7t+3(7-r)=-(r+4) | | 12(x+3)=4(3x+1)+32 | | -7.5(2y+4)-2.9(3y-6)= | | 2x+x=145 | | x+.625=.25 | | 33x^2-12x+5x=0 | | 3.4x=2.6x+4.0 | | 0.80x+0.50(2-x)=0.10(-74) | | 9=-63v+(-54) | | 5j+5=t-2 |